ANALISIS PERBANDINGAN KREDIT PEMILIKAN RUMAH (KPR) PADA PT. BANK CENTRAL ASIA TBK PALEMBANG DENGAN PT. BANK CENTRAL ASIA SYARIAH DI PALEMBANG - Kemas Welly Angga Permana (Jurnal Media Ekonomi (JURMEK), 2020)
Comparative Analysis of Home Ownership Loans (KPR) at PT. Bank Central Asia, Tbk Palembang with PT. Bank Central Asia Syariah in Palembang / Accounting Information System The formulation of the problem is how the comparison of KPR loan interest rates at PT. Bank Central Asia, Tbk Palembang with PT. Bank Central Asia Syariah Palembang. The goal is to find out the interest rates for conventional bank housing loans (KPR) at PT. Bank Central Asia, Tbk Demang Branch Palembang and Sharia bank at PT. Bank Central Asia Syariah Palembang and know which mortgage interest rates are lower between conventional BCA and BCA Syariah. This study uses descriptive analysis to determine the mortgage interest rate (KPR) at PT. Bank Central Asia, Tbk Demang Branch Palembang with PT. Bank Central Asia Syariah Branch Office in Palembang for the period of 2019. The results of the research on the provision of credit at conventional BCA banks and BCA Syariah banks do not have much difference in the procedures and requirements file, it's just that the interest rate or the BCA Syariah bank called margin (interest rate) has a significant difference. The interest rate for conventional BCA is lower than for BCA Syariah.